Avalanche Multiplication and Excess Noise Factor of Heterojunction Avalanche Photodiodes - You, A. H.; Low, L. C.; Cheang, P. L. (2006)
A Monte Carlo (MC) model to compute the statistics of avalanche multiplication and excess noise factor in heterojunction avalanche photodiode (HAPD) is presented. The proposed model is able to simulate the multiplication gain and excess noise factor incorporating the dead-space effect, band-edge discontinuity and hole to electron ionization ratio in HAPDs. The deadspace effect is included in our model, which has been shown to play an important role in reducing noise in homojunction APDs. It is shown that the dead-space effect also reduces the avalanche noise in heterojunction devices. We demonstrate that the dead-space effect and feedback impact ionization are the dominant effects to improve the excess noise factor in HAPDs.